Pengaruh Struktur Aktiva dan Profitabilitas terhadap Struktur Modal Perusahaan Makanan dan Minuman - Kanita, Ghia Ghaida (TRIKONOMIKA, 2014)
This study aims to determine whether the asset structure and profitability have an influence on the capital structure. The object of research is taken from food and beverage companies listed in Indonesia Stock Exchange 2007-2009 period. The method used in this research is descriptive verification, regression equation used is a model of the data panel. The result of this research is the asset structure has no significant effect on capital structure, while profitability has a significant impact on the capital structure of food and beverage companies listed on the Stock Exchange 2007-2009 period.